PRODUCTION OF DOUBLED HAPLOID RICE PLANTS (ORYZA SATIVA L.) BY ANTHER CULTURE. - REIFFERS, ISABELLE; ADELSON B. FREIRE
The results of anther culture of F1 pollen issued from 23 single crosses are presentes. A relation between the morphology of the panicle and the microspore stage was established. After cold-pretreatment (8 days at 4ºC), the anthers were cultured on the callus-induction medium N6 supplemented with 1 mg 1 - 1 naphthaleneacetic acid. The calli were transferred to MS plant regeneration medium supplemented with 3mgl-1 kinetin + 0.5 mg l-1 naphthaleneacetic acid. The induction frequency varied from 0.22% to 29% and the regeneration frequency from 0% to 144.4%, dependent upon the crosses used. On average, 27% of the plants obtained were albinos and 59% of the green plants underwent spontaneous chromosome doubling, Thirty- nine doubled haploid lines were evaluated and multiplied in the field. Lines with an excellent behaviour in upland culture conditions were selected from two crosses.
Keywords: ARROZ; ORYZA SATIVA; HAPLOIDA; CULTIVO DE ANTERAS Y TEJIDOS; BIOTECNOLOGIA; Artículos de revista